1998
DOI: 10.1148/radiology.207.1.9530307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT and MR imaging in staging of neck metastases.

Abstract: CT performed slightly better than MR imaging for all interpretative criteria. However, a high NPV was achieved only when a low size criterion was used and was therefore associated with a relatively low PPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
163
3
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(178 citation statements)
references
References 0 publications
6
163
3
6
Order By: Relevance
“…Therefore, we used the 1-cm size to indicate a positive node. The positive predictive value of this criterion was only 50% in the study of Curtin et al (1998). This low value might explain our good results in cases with M1 LYM disease, although all 15 patients with M1 LYM disease had advanced T3 or T4 disease with severe stricture.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Therefore, we used the 1-cm size to indicate a positive node. The positive predictive value of this criterion was only 50% in the study of Curtin et al (1998). This low value might explain our good results in cases with M1 LYM disease, although all 15 patients with M1 LYM disease had advanced T3 or T4 disease with severe stricture.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, we modified the criteria described previously for the definition of T3 disease (Picus et al, 1983) to include tumours attached to the organs at a p901 angle to the thoracic aorta as observed on the CT scan. The patients were considered to have LYM if the tumour was X1 cm in diameter (Curtin et al, 1998). Radiological evaluations for staging were reviewed by two radiologists (TK and YM) and the physicians at Showa University School of Medicine, as was reported in previous studies (Picus et al, 1983;Takashima et al, 1991;Curtin et al, 1998).…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently used criteria for differentiation between benign and malignant lymph nodes are the presence of necrosis-mainly seen in larger lymph nodes-and assessment of lymph node morphology such as borders and internal heterogeneity [9,10]. Also the introduction of lymph node specific contrast agents like ultrasmall particles iron oxide on magnetic resonance imaging (MRI) provides differentiation between benign and malignant lymph nodes in the head and neck and results are improving [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that END significantly improved lymph node 27 , and it occurs primarily in lymph nodes approximating 20.0 mm or greater 28 . It is also quite rare and not often visible in small lymph nodes 29,30 . The generally used upper limit of normal for the greatest nodal diameter is 1.5 cm for level I and II nodes, and 1 cm for all other levels.…”
Section: Discussionmentioning
confidence: 99%